Golden boy - Sullivan, Tara. (New York, NY : G.P. Putnam's Sons, an imprint of Penguin Group (USA) Inc., 2013)
A Tanzanian albino boy finds himself the ultimate outsider, hunted because of the color of his skin.
Keywords: Albinos and albinism -- Juvenile fiction; Human skin color -- Juvenile fiction; Human rights -- Juvenile fiction; Survival -- Juvenile fiction; Tanzania -- Juvenile fiction